بيع العربون وتطبيقاته المعاصرة - فردوس, خضير (University of Eloued جامعة الوادي, 2019)
يعالج هذا البحث موضوعا مهما في عالم المعاملات المالية المعاصرة ألا وهو "بيع العربون وتطبيقاته المعاصرة"، وإشكاليته تمثلت في: مدى توظيف بيع العربون في المعاملات المالية المعاصرة، وقد جاء الموضوع في مقدمة وثلاثة مباحث وخاتمة؛حيث افتتح بالمقدمة التي كانت كنظرة شاملة للبحث من حيث أهميته وأسباب اختياره والدراسات السابقة فيه وغيرها، وخُصِّصَ المبحث الأول لمفهوم بيع العربون وأدلةُ مشروعيته والفرق بينه وبين المصطلحات المشابهة له، أما الثاني ففيه التطبيـــقات المعاصرة لبيع العربـــون في عمليات المصارف الإسلامية من صرف ومرابحة، وجُعِلَ الثالث لدراسة التطبيقات المعاصرة لبيع العربون في عمليات الأسواق المالية، وختمته بجملة من النتائج أهمها أنَّ صورة بيع العربون هو أن يدفع المشتري إلى البائع جزءاً من الثمن؛ على أنه إن تم البيع فالعربون من جملة الثمن، وإن لم يتم فالعربون من نصيب البائع، والرأي الراجح في بيع العربون والذي عليه أكثر العلماء المعاصرين هو الجواز بشرط التوقيت، عملاً بالوقائع الكثيرة التي دلت على جوازه في عصر الصحابة والتابعين. This research deals with an important subject in the world of contemporary financial transactions, namely "the sale of deposits and its contemporary applications". The problematic was in the extent to which the sale of deposits is used in modern financial transactions. The study consists of an introduction, three chapters and a conclusion. It openswith the introduction which was a comprehensive view of the research in terms of importance, reasons for selection and relevant previous studies. The first chapter is devoted to the concept of sale of deposits, evidence of its legality and the difference between it and similar terms. The second chapter is about the contemporary applications to sell deposits in the operations of Islamic banks, exchange and usury. The third chapter is to study contemporary applications for the sale of deposits in the operations of financial markets. The study concludes with a number of results, the most important of which is that the sale of deposits is that the buyer pays the seller part of the price; if the sale is made, the deposit is a part of the price; if not, then it is for the seller. The most correct opinion in the sale of deposits, which is recommended by most modern scholars is that it is permitted yet conditioned with the timing, in accordance with the many facts that indicated its permissibility in the era of Companions and followers.
مذكرة ماستر تخصص فقه مقارن
Keywords: العربون – المرابحة – الصرف- الأسهم; Brokers - Murabaha - Exchange - Shares